Public attitudes towards a European minimum income benefit: How (perceived) welfare state performance and expectations shape popular support. (October 2020) - Baute, Sharon; Meuleman, Bart
The economic crisis and the unequal degree to which it has affected European Union (EU) member states have fuelled the debate on whether the EU should take responsibility for the living standards of European citizens. The current article contributes to this debate by investigating for the first time public support for an EU-wide minimum income benefit scheme. Through an analysis of data from the European Social Survey 2016, our results reveal that diverging national experiences and expectations are crucial in understanding why Europeans are widely divided on the implementation of such a benefit scheme. The analysis shows that (1) welfare state generosity and perceived welfare state performance dampen support, (2) those expecting that 'more Europe' will increase social protection levels are much more supportive, (3) the stronger support for a European minimum income benefit in less generous welfare states is explained by more optimistic expectations about the EU's domestic impact and (4) lower socioeconomic status groups are more supportive of this policy proposal. These findings can be interpreted in terms of sociotropic and egocentric self-interests, and illustrate how (perceived) performance of the national welfare state and expectations about the EU's impact on social protection levels shape support for supranational social policymaking.